Effects of moso bamboo and Sedum plumbizincicola intercropping on transport and accumulation of Cu, Cd and Zn in soil-plant system - LIU Chen; GUO Jia; ZHAO Min; ZHONG Bin; GUO Hua; HOU Shuzhen; XU Weijie; YANG Yun; WANG Renyuan; YE Zhengqian; LIU Dan (浙江大学学报. 农业与生命科学版)
Phytoremediation is a low-cost and eco-friendly technology by using plants to uptake and accumulate heavy metals from contaminated soils. Intercropping is a simple and feasible method of agricultural management which was applied here to increase plant production and facilitate the efficiency of phytoremediation.A pot experiment based on an intercropping system of moso bamboo seedlings and Sedum plumbizincicola was conducted to investigate its influence on the growth of plants, transfer ability of heavy metals in the system of soil and plant, and the effect on accumulation of Cu, Cd and Zn in different parts of plant.The results showed that the root biomass of S. plumbizincicola which was intercropped with moso bamboo in 2 mm soil decreased significantly, and the biomass of both stems and leaves of moso bamboo which was intercropped with S. plumbizincicola in 5 mm soil was also declined clearly compared with that of moso bamboo in 2 mm soil. Moreover, the biomass of moso bamboo seedlings and S. plumbizincicola was reduced as compared with those of CK (monocropping), which suggested that intercropping led to competition between moso bamboo seedlings and S. plumbizincicola. Intercropping resulted in the decline of heavy metal uptake for the roots of moso bamboo seedlings and the competition between Cd and Zn in the roots of S. plumbizincicola, while it improved both upward transport by roots, but there were differences in the process for different metals accumulated in different parts (stem or leaf) of moso bamboo seedlings. In addition, contrast to monocropping, Cu, Cd and Zn accumulation in any part of moso bamboo seedlings decreased distinctly, but Cd and Zn accumulation in the overground part of S. plumbizincicola increased by 57% and 82% in 5 mm soil.In sum, the intercropping system of moso bamboo and S. plumbizincicola shows the potential of upward transfer of heavy metals, and it also has positive impacts on Cu, Cd and Zn accumulation.